Anti-inflammatory and hepatoprotective effects of Moringa oleifera fruit in obesity-induced liver injury - Susantiningsih, Tiwuk; Thadeus, Maria Selvester; Citrawati, Mila; Setyaningsih, Yuni (Universitas Muhammadiyah Purwokerto, 2026)
Background: Hepatic metabolic disorders are closely associated with obesity and are characterized by systemic inflammation and liver injury. Moringa oleifera fruit contains various bioactive compounds with potential anti-inflammatory and hepatoprotective properties. However, evidence regarding its effects on obesity-induced liver injury remains limited.. Objective: This study aimed to evaluate the anti-inflammatory and hepatoprotective effects of Moringa oleifera fruit extract in an obesity-induced rat model.. Methods: This experimental study used 30 male Sprague-Dawley rats divided into five groups: normal control (N), obese control (O), obese rats treated with Moringa oleifera fruit extract at 500 mg/kg body weight once daily (OEMO1), twice daily (OEMO2), and obese rats treated with vitamin C (OC). Systemic inflammation was assessed by measuring serum C-reactive protein (CRP) levels using ELISA, while hepatic changes were evaluated through biochemical markers and histopathological analysis. Data were analyzed using one-way ANOVA followed by post hoc testing. Results: Obese rats exhibited significantly elevated serum CRP levels and marked hepatic alterations compared to normal controls (p < 0.05). Administration of Moringa oleifera fruit extract significantly reduced CRP levels and improved hepatic histoarchitecture in obese rats, with the greatest effect observed in the twice-daily treatment group (OEMO2) (p < 0.05). The effects were comparable to or greater than those observed with vitamin C. Conclusions: Moringa oleifera fruit extract demonstrates significant anti-inflammatory and hepatoprotective effects in an obesity-induced rat model, suggesting its potential as a natural therapeutic agent for obesity-related liver injury.